Politeness Strategies Used by the Community of SMKN 3 Enrekang in Daily Conversation - Muhammad Syamsir; Kasmiati Abunawar; Nur Kumalasari; Nurhana Nurhana (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This paper discusses about politeness strategies and some factors influencing polite strategies to be used in the community of SMK Negeri 3 Enrekang, where it is identified as one of Bugis community in South Sulawesi. This was based on the observation we conducted in some circumstances of conversation between students, teachers, staff, and canteen keeper. In collecting data, we employed ethnography of communication using some strategies such as participant observation, informal interview, and recording conversation. The result of this study showed that there were four kinds of strategies used by the communities of SMKN 3 Enrekang, they were bald-on record, positive politeness, negative politeness, off record (indirect). It can be seen from the use of pronoun such ki’ and ta’ or mu’ and ‘ko’ and other particular words which show politeness strategies. The factors influencing politeness strategy were social status, age, intimacy, and solidarity.